Assessment of vibratory QST abnormality in diabetic patients with special correlation to duration of diabetes - Saha, Kaushik; Saha, Dipa (International Journal of Advances in Medicine, 2020)
Background: Peripheral Neuropathy is one of the common microvascular complications in diabetes mellitus affecting both large and small nerve fibres. In present study we have assessed the impairment of vibration perception threshold (VPT) QST that enables evaluation of affection of large myelinated (Aα and Aβ) fibres. Methods: Authors used Biothesiometer in our study that served a satisfactory tool for quantitating vibratory sense. In our study 120 diabetic patients between 30 to 60 yrs age group with duration of illness ≤10 yrs, 10-20 years and more than 20 years were subjected to Vibratory QST by instrument (Vibrotherm Dx) at several specific points of feet. Results: The result observed is, 73.2% (n=22) diabetics with clinical neuropathy show impairment of vibration sense, while 60% of diabetic patients without clinical neuropathy also show impairment of vibration sense. Result suggests involvement of nerve fibres in a subclinical stage in diabetic patients. Relation between vibratory QST and duration of diabetes is also established, Chi-square trend test is done and it shows there is positive trend with duration of diabetes and it is statistically significant p≤0.001. Conclusions: This study suggests that Vibratory QST should be carried out in every diabetic patient irrespective of clinical neuropathy and duration of diabetes, for early detection, progression & institution of therapy.